(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article considers strategies and language tools for realization of politeness category in the newspaper text. There are strategies of positive and negative categories of politeness, proposed by different researchers. The author dwells on the stylistic peculiarities of the newspaper text, which stipulate the realization of politeness in the newspaper language. Attention is paid to the fact that indication of the subjectivity of the journalist’s opinion is one of the ways of reducing the statement categoricity. The harmonic interaction does not assume the categoricity of the communicators’ opinion. It is noted that speech acts of excuse and apology are often met in paper text. They are related to strategies of negative politeness. The usage of these strategies is connected with «concern» for the addressee and, finally, with effective realization of communicational intentions.